Dynamics of Ma’arif Nahdlatul Ulama Education Institute - Purnomo, Suryo Setio; Ansori, M. Afif; Andari, An An (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This research aims to examine how the dynamics of Ma'arif Nahdlatul Ulama Education Institute contribute and make a major contribution to the progress of the Indonesian nation. The research was written based on a literature review and in-depth understanding and accumulated understanding from various trusted primary book sources. This research type is qualitative with a Library Research approach. Data collection techniques are carried out using documentation. Data sources come from books and journals. The data analysis technique uses Content Analysis. The study results show that in developing education, NU has many Islamic boarding schools and madrasas spread across the country and also has public schools from kindergartens to universities. NU formed Rabithah Ma'ahid al-Islamiyah (RMI) to implement NU policies in the field of developing Islamic boarding schools and formed the Education and Ma'arif Institute to implement NU policies in the education field and teaching, both formal and nonformal, apart from Islamic boarding schools. The forms of education institutes at NU include Islamic boarding schools, madrasas, schools, and colleges. It is in this context that NU is making every effort to improve and develop its education while encouraging religious values, especially in the field of ahlu al-sunnah wa al-jama'ah, teaching optimally to obtain optimal results by improving the quality of teaching staff through training so that they are able to master various learning strategies, be empowered and able to be creative in the making/using literacy learning media by implementing technology in learning.